2020
DOI: 10.1182/bloodadvances.2019001330
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic syndrome unrelated to lentiviral vector in a patient treated with gene therapy for sickle cell disease

Abstract: Key Points Ability to accurately attribute adverse events post–gene therapy is required to describe the benefit-risk of these novel treatments. A SCD patient developed myelodysplastic syndrome post-LentiGlobin treatment; we show how insertional oncogenesis was excluded as the cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 31 publications
0
80
0
1
Order By: Relevance
“…32 Of note, an earlier case of MDS was also reported in a sickle cell patient but multiple independent assays demonstrated the absence of vector integration in the CD341 blasts and excluded lentiviral vectormediated oncogenesis as the MDS cause. 33 Several other gene insertion approaches and vectors have also been evaluated in animal models and validated for clinical investigation. A phase 1/2 trial (TIGET-BTHAL, NCT02453477) in TDT patients with β 0 or severe β+ mutations using an intrabone administration of HSCs transduced with the lentiviral vector GLOBE showed transfusion reduction in three adults and complete independence in 3/4 evaluated children.…”
Section: Gene Insertionmentioning
confidence: 99%
“…32 Of note, an earlier case of MDS was also reported in a sickle cell patient but multiple independent assays demonstrated the absence of vector integration in the CD341 blasts and excluded lentiviral vectormediated oncogenesis as the MDS cause. 33 Several other gene insertion approaches and vectors have also been evaluated in animal models and validated for clinical investigation. A phase 1/2 trial (TIGET-BTHAL, NCT02453477) in TDT patients with β 0 or severe β+ mutations using an intrabone administration of HSCs transduced with the lentiviral vector GLOBE showed transfusion reduction in three adults and complete independence in 3/4 evaluated children.…”
Section: Gene Insertionmentioning
confidence: 99%
“…However, larger studies and longer follow-up are needed to carefully assess the clinical e cacy and safety of gene editing based approaches. The occurrence of a secondary tumor (myelodysplasia followed by leukemia) in one SCD patient treated with LV 27 , likely as a result of chemotherapy-induced mutagenesis on residual host cells as well as a bone marrow dysplasia observed in an ADA-SCID patient treated with γRV deriving from non-corrected cells 28 were not unexpected. Indeed, the risk of secondary tumors is reported to be 4% at 7 years after autologous HSCT, with a median onset of 2.5 years post-transplantation (range = 3 months-7 years).…”
Section: Discussionmentioning
confidence: 86%
“…63 A case of MDS in a SCD patient treated in the HGB-206 trial, who did not have MDS before myeloablation, was also observed. 64 The absence of vector integration in CD34+ blasts excludes lentiviral vector-mediated oncogenesis. An even more recent press release from Bluebird bio on March 10, 2021, announced that, according to the analyses, lentiviral vector BB305 unlikely caused the AML.…”
Section: Gene Therapy and Gene Editingmentioning
confidence: 99%